# Solve for x 6^(x-4)=y^(3+66) 6x-4=y3+66
Take the natural logarithm of both sides of the equation to remove the variable from the exponent.
ln(6x-4)=ln(y3+66)
Expand ln(6x-4) by moving x-4 outside the logarithm.
(x-4)ln(6)=ln(y3+66)
Apply the distributive property.
xln(6)-4ln(6)=ln(y3+66)
Add 3 and 66.
xln(6)-4ln(6)=ln(y69)
Move all the terms containing a logarithm to the left side of the equation.
xln(6)-4ln(6)-ln(y69)=0
Move all terms not containing x to the right side of the equation.
Add 4ln(6) to both sides of the equation.
xln(6)-ln(y69)=4ln(6)
Add ln(y69) to both sides of the equation.
xln(6)=4ln(6)+ln(y69)
xln(6)=4ln(6)+ln(y69)
Divide each term by ln(6) and simplify.
Divide each term in xln(6)=4ln(6)+ln(y69) by ln(6).
xln(6)ln(6)=4ln(6)ln(6)+ln(y69)ln(6)
Cancel the common factor of ln(6).
Cancel the common factor.
xln(6)ln(6)=4ln(6)ln(6)+ln(y69)ln(6)
Divide x by 1.
x=4ln(6)ln(6)+ln(y69)ln(6)
x=4ln(6)ln(6)+ln(y69)ln(6)
Cancel the common factor of ln(6).
Cancel the common factor.
x=4ln(6)ln(6)+ln(y69)ln(6)
Divide 4 by 1.
x=4+ln(y69)ln(6)
x=4+ln(y69)ln(6)
x=4+ln(y69)ln(6)
Solve for x 6^(x-4)=y^(3+66)   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top